Local and systemic therapy of recurrent ependymoma in children and adolescents: short- and long-term results of the E-HIT-REZ 2005 study. Issue 6 (17th December 2020) - Adolph, Jonas E; Fleischhack, Gudrun; Mikasch, Ruth; Zeller, Julia; Warmuth-Metz, Monika; Bison, Brigitte; Mynarek, Martin; Rutkowski, Stefan; Schüller, Ulrich; von Hoff, Katja; Obrecht, Denise; Pietsch, Torsten; et al.
Abstract: Background: Survival in recurrent ependymomas in children and adolescents mainly depends on the extent of resection. Studies on repeated radiotherapy and chemotherapy at relapse have shown conflicting results. Methods: Using data from the German multi-center E-HIT-REZ-2005 study, we examined the role of local therapy and the efficacy of chemotherapy with blockwise temozolomide (TMZ) in children and adolescents with recurrent ependymomas. Results: Fifty-three patients with a median age of 6.9 years (1.25–25.4) at first recurrence and a median follow-up time of 36 months (2–115) were recruited. Gross- and near-total resection (GTR/NTR) were achieved in 34 (64.2%) patients and associated with a markedly improved 5-year overall survival (OS) of 48.7% vs. 5.3% in less than GTR/NTR. Radiotherapy showed no improvement in OS following complete resection (OS: 70 (CI: 19.9–120.1) vs. 95 (CI: 20.7–169.4) months), but an advantage was found in less than GTR/NTR (OS: 22 (CI: 12.7–31.3) vs. 7 (CI: 0–15.8) months). Following the application of TMZ, disease progression was observed in most evaluable cases (18/21). A subsequent change to oral etoposide and trofosfamide showed no improved response. PF-A EPN were most abundant in relapses ( n = 27). RELA-positive EPN ( n = 5) had a 5-year OS of 0%. Conclusion: The extent of resection is the most important predictor of survival at relapse. Focal re-irradiation is a useful approach if complete resection cannot be achieved, but no additional benefit was seen after GTR/NTR. Longer-term disease stabilization (>6 months) mediated by TMZ occurred in a small number of cases (14.3%).